2013
DOI: 10.4194/1303-2712-v13_3_09
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was conducted to determine the effects of various lengths of starvation periods on following compensatory growth (CG) in rainbow trout under summer conditions (18.1°C and day length of 12.5-14.5 hours). Five treatments with triplicate tanks were as follows: control (C) fed to satiation over 84 days; one (S1), two (S2), three (S3), and four (S4) weeks of starvation; and then refeeding for the remaining eight weeks of the experiment. Starvation periods induced hyperphagia during refeeding but only S1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
(109 reference statements)
1
6
2
Order By: Relevance
“…In our study, protein efficiency ratios were affected by feeding regimes. PER values did not significantly change in single and multiple cycle fed Atlantic halibut (Heide et al, 2006), varied cycle fed olive flounder (Cho and Cho, 2009) and single cycle fed rainbow trout (Sevgili et al, 2013). However, some studies have reported that PER values were affected by feeding model during compensation growth, as is the case in our study (Ali and Jauncey, 2004;Cho et al, 2006, Eroldoğan et al, 2008.…”
Section: Figurecontrasting
confidence: 51%
See 1 more Smart Citation
“…In our study, protein efficiency ratios were affected by feeding regimes. PER values did not significantly change in single and multiple cycle fed Atlantic halibut (Heide et al, 2006), varied cycle fed olive flounder (Cho and Cho, 2009) and single cycle fed rainbow trout (Sevgili et al, 2013). However, some studies have reported that PER values were affected by feeding model during compensation growth, as is the case in our study (Ali and Jauncey, 2004;Cho et al, 2006, Eroldoğan et al, 2008.…”
Section: Figurecontrasting
confidence: 51%
“…*The first 10-day FI values of group G3 were not calculated because the group was in 10-day starvation group and not fed. et al, 2012;Sevgili et al, 2013). In this comprehensive study, both single and multiple starvation and refeeding cycles were applied and short and long term starvation periods were tested alongside each other.…”
Section: Figurementioning
confidence: 99%
“…Similarly, in this study, hyperphagia was observed after 1 and 2 weeks of starvation. There are numerous studies reporting hyperphagia as the main mechanism of compensatory growth in fish (Blake, Inglis, & Chan, 2006;Boujard, Burel, Médale, Haylor, & Moisan, 2000;Dobson, & Holmes, 1984;Miglavs, & Jobling, 1989;Qian et al, 2000;Quinton, & Blake, 1990;Sevgili et al, 2013;Xiao et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In their study Yılmaz (2012) reported that there was no difference between the control group and other groups (B) and (C) in terms of feed conversion rates, and there was a difference between the groups of (D) and (E). In their study, in which they investigated the effects of starvations periods of different lengths on compensatory growth in rainbow trout, Sevgili et al (2013), applied the feeding periods of 1, 2, 3 and 4 weeks of starvation/8 weeks feeding. There was no difference between the values of feed conversion rates among these groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation